A polymorphism in miR‐1262 regulatory region confers the risk of lung cancer in Chinese population. Issue 5 (29th May 2017) - Xie, Kaipeng; Chen, Mengxi; Zhu, Meng; Wang, Cheng; Qin, Na; Liang, Cheng; Song, Ci; Dai, Juncheng; Jin, Guangfu; Shen, Hongbing; Lin, Dongxin; Ma, Hongxia; et al.
Abstract : It has been proposed that the majority of disease‐associated loci identified by genome‐wide association studies (GWAS) are enriched in non‐coding regions, such as the promoter, enhancer or non‐coding RNA genes. Thus, we performed a two‐stage case‐control study to systematically evaluate the association of genetic variants in miRNA regulatory regions (promoter and enhancer) with lung cancer risk in 7, 763 subjects (discovery stage: 2, 331 cases and 3, 077 controls; validation stage: 1, 065 cases and 1, 290 controls). As a result, we identified that rs12740674 (C > T) in miR‐1262 enhancer was significantly associated with the increased risk of lung cancer (additive model in discovery stage: adjusted OR = 1.31, 95%CI = 1.13–1.53, p  = 3.846 × 10 −4 in Nanjing GWAS; adjusted OR = 1.20, 95%CI = 1.00–1.44, p  = 0.041 in Beijing GWAS; validation stage: adjusted OR = 1.20, 95%CI = 1.03–1.41, p  = 0.024). In meta‐analysis, the p value for the association between rs12740674 and lung cancer risk reached 6.204 × 10 −6 (adjusted OR = 1.24, 95%CI = 1.13–1.36). Using 3DSNP database, The Cancer Genome Atlas (TCGA) data and functional assays, we observed that the risk T allele of rs12740674 reduced the expression level of miR‐1262 in lung tissue through chromosomal looping, and overexpression of miR‐1262 inhibited lung cancer cell proliferation probably through targeting the expression levels of ULK1 and RAB3D . Our findings confirmed the important role that genetic variants of noncoding sequence play in lung cancer susceptibility and indicated that rs12740674 in miR‐1262 may be biologically relevant to lung carcinogenesis. Abstract : What's new? It has been proposed that most disease‐associated loci identified by genome‐wide association studies are enriched in non‐coding regions. Here, the authors performed a two‐stage case‐control study to evaluate the association of genetic variants in miRNA regulatory regions with lung cancer risk in a large population. They found that rs12740674 in miR‐1262 enhancer was significantly associated with increased risk of lung cancer. Using The Cancer Genome Atlas and 3DSNP databases and functional assays, they observed that the risk allele reduced miR‐1262 expression in lung tissue through chromosomal looping. miR‐1262 overexpression inhibited lung cancer cell proliferation through modulating ULK1 and RAB3D expression.